2018
DOI: 10.1080/13218719.2018.1507844
|View full text |Cite
|
Sign up to set email alerts
|

Does eyewitness and interviewer gender influence children’s reports? An experimental analysis of eyewitness and interviewer gender on children’s testimony

Abstract: This study examines how children's age, gender and interviewer gender affected children's testimony after witnessing a theft. Children (N ¼ 127, age ¼ 6-11 years) witnessed an experimenter (E1) find money, which he/she may/may not have taken. E1 then asked the children to falsely deny that the theft occurred, falsely accuse E1 of taking the money, or tell the truth when interviewed by a second experimenter. Falsely denying or falsely accusing influenced children's forthcomingness and quality of their testimony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 79 publications
1
5
0
Order By: Relevance
“…First, this study examined whether age was a significant predictor of disclosing behaviours. In line with findings from previous research (Foster et al, 2019;Wyman et al, 2019), all models found that age was associated with disclosure of the mock crime. Older children (i.e., 10-13 years of age) were more likely to tell the truth compared to younger children (i.e., 7-9 years of age) at the end of the interview.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, this study examined whether age was a significant predictor of disclosing behaviours. In line with findings from previous research (Foster et al, 2019;Wyman et al, 2019), all models found that age was associated with disclosure of the mock crime. Older children (i.e., 10-13 years of age) were more likely to tell the truth compared to younger children (i.e., 7-9 years of age) at the end of the interview.…”
Section: Discussionsupporting
confidence: 90%
“…Lying and its emergence in early childhood have been extensively studied as part of children’s normative development (Lyon et al, 2014; Talwar & Crossman, 2011, 2012). Altogether, literature on the developmental course of lie telling has provided insights on the age of onset of lie telling in children (e.g., Evans & Lee, 2013; Talwar & Lee, 2008), the frequency of their deceptive behaviours (e.g., Evans et al, 2011), the types of lies told (e.g., Talwar & Crossman, 2011), and the complexity of children’s lies (e.g., Foster et al, 2019; Talwar et al, 2007). From a behavioural perspective, lying is a common social phenomenon in both children and adults and appears to emerge in the preschool years as a function of normative cognitive development and develops through the elementary school years (Talwar & Crossman, 2011).…”
Section: Developmental Course Of Lie Telling and Secret Keepingmentioning
confidence: 99%
“…The current study aims to conduct a comprehensive examination of the differences between children's true and false statements about a high-cost event obtained using an interview incorporating cognitive instructions. Many studies have examined children's lie-telling about low-cost events (e.g., Saykaly et al, 2016;Talwar et al, 2004Talwar et al, , 2016, but few (e.g., Foster et al, 2019;Tye et al, 1999) have done so with high-cost events that mimic those that children may experience and be asked to report on in real life, such as being a victim of abuse, or witnessing a crime (Lyon, 1999). Factors that influence children's lietelling in a high-stakes scenario may differ from those that influence their lie-telling in a low-stakes scenario; therefore, it is important to examine children's lie-telling tendencies and abilities in a high-stakes scenario (Foster et al, 2019).…”
Section: Present Studymentioning
confidence: 99%
“…Many studies have examined children's lie-telling about low-cost events (e.g., Saykaly et al, 2016;Talwar et al, 2004Talwar et al, , 2016, but few (e.g., Foster et al, 2019;Tye et al, 1999) have done so with high-cost events that mimic those that children may experience and be asked to report on in real life, such as being a victim of abuse, or witnessing a crime (Lyon, 1999). Factors that influence children's lietelling in a high-stakes scenario may differ from those that influence their lie-telling in a low-stakes scenario; therefore, it is important to examine children's lie-telling tendencies and abilities in a high-stakes scenario (Foster et al, 2019). In the current study, the high-stakes scenario was a theft; although witnessing a theft does not have the same effects on children as experiencing abuse does, all children are aware that stealing is a serious transgression.…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation